Among the water-soluble vitamins, dietary intakes of vitamins C, B2 and folate are associated with the reduced risk of diabetes in Japanese women but not men. Issue 12 (10th June 2019) - Eshak, Ehab S.; Iso, Hiroyasu; Muraki, Isao; Tamakoshi, Akiko
Abstract: Recent studies have shown that micronutrients are involved in the pathology of type 2 diabetes. Antioxidant effects of vitamins C and B2 and homocysteine-lowering effects of vitamins B6, folate and B12 may have protective roles. However, a few reports have investigated the association between dietary water-soluble vitamin intakes and risk of diabetes. In a prospective study encompassing 19 168 healthy Japanese men and women aged 40–79 years, we examined the associations between dietary intakes of water-soluble vitamins, determined by a validated self-administered FFQ, with the risk of 5-year cumulative incidence of type 2 diabetes by using the logistic regression model. Within the 5-year period, there were 494 self-reported new cases of diabetes. Higher dietary intakes of vitamins C, B2 and folate were associated with lower risk of incident diabetes only in women, whereas no associations of dietary intakes of vitamins B1, B3, B5, B6 and B12 were observed in either sex. The multivariable OR in the highest v . the lowest quartile of intakes among women were 0·61 (95 % CI 0·44, 0·94; P -trend = 0·04) for vitamin C, 0·56 (95 % CI 0·34, 0·93; P -trend = 0·03) for vitamin B2 and 0·70 (95 % CI 0·46, 0·98; P -trend = 0·03) for folate. Other than that for sex ( P < 0·05), the P -interactions with age, BMI, smoking status or having a family history of diabetes were >0·10. In conclusion, higher dietary intakes of vitamins C, B2 and folate, but not other water-soluble vitamins, were associated with reduced risk of type 2 diabetes in Japanese women.